Menstrual Cycle Hormone Changes Associated with Menstrual Cycle Interval in 9-18-year-old girls - Naeimeh Tayebi; Maryam Keshavarz; Mohammad Hossain Dabbaghmanesh; Marzieh Akbarzadeh (Mashhad University of Medical Sciences, 2022)
Background & aim: Hormonal disorders may be associated with a variety of menstrual disorders that can have different health consequences and are an indicator women's gynecologic health. The aim of this study was to evaluate the pattern of sexhormones of the menstrual cycle related to the menstrual cycle intervals in girls aged 9-18 years.Methods: In this two-stage cross-sectional study, 2000 girls aged 9-18 years old in first stage were selected conveniently from four districts of Shiraz, Iran in cluster form in 2015, and their pattern of menarche age (early, normal, late) was determined. In the second stage, 50 students with normal menarche and 12 students with late menarche were selected and each completed a questionnaireincluding demographic characteristics, Hygam chart and menstrual bleeding characteristics (using Smith-Di Giulio criterion) questionnaire. Their hormones including TSH, Prolactin, FSH, DHEAS and Testosterone were also measured.Results: The highest frequency of age was 16 years (40.3%) and the lowest was 17 years old (8.1%). The results of one-way analysis of variance between different hormones and menstrual cycle interval showed that there is a significant relationshipbetween TSH (P=0.03), Prolactin (P=0.002) and menstrual intervals. But no significant relationship was seen between LH (P=0.63), FSH (P=0.08), DHEAS (P=0.82), Testosterone (P=0.703) and menstrual intervals.Conclusion: TSH and prolactin disorders are the most common hormonal disorders in girls with menstrual disorders. It is recommended to check these hormones in girls with various menstrual disorders after eliminating structural disorders and before starting different treatments for menstrual disorders